Is 48-hour targeted temperature management not superior to 24-hour targeted temperature management after out-of-hospital cardiac arrest in adults? Feasible but still inconclusive - Lee, Seung-Joon; Kim, Young-Min (Journal of Emergency and Critical Care Medicine, 2017)
Since positive results of a quasi-randomized controlled trial and a randomized controlled trial were reported in 2002, mild therapeutic hypothermia (TH) has been accepted as an intervention to improve both survival and neurological outcomes following out-of-hospital cardiac arrest (OHCA) with shockable rhythm and has been actively implemented for all cardiac arrest patients around the world over the past decade (1,2). However, many questions for the optimal use of mild TH remain unresolved. Some researchers asserted that the scientific evidence is not sufficient to use mild TH for comatose survivors after cardiac arrest and have undertaken well-designed randomized controlled trials (RCTs) to demonstrate the efficacy and to determine an optimal dose for this intervention (3,4). In 2013, the largest trial including 939 patients after OHCA that compared a target temperature of 33 vs. 36 ℃ found no difference in 6-month mortality between the two temperatures (4). The results of the trial cast doubt on the efficacy of mild TH, and a following trial comparing targeted temperature management (TTM) at 33 ℃ with standard normothermia care (